Stress exposure from in-utero to adolescence, the HPA-axis response to stress, and symptoms of depression and anxiety in adulthood - McLaughlin, Carly (Curtin University, 2022)
This doctoral thesis used a prospective design in a series of four studies to investigate links between common early-life stress exposures, from in-utero to age 17, alterations in the HPA-axis physiological response to a stressor at age 18, and depression and anxiety symptoms at age 20, with consideration of sex differences. Findings are important as they may help inform the timing of intervention and support strategies for reducing exposure to early-life stress.